La calidad de servicio en la satisfacción de los usuarios: Caso polideportivo - Paredes Cruz, Jesús Gonzalo (2022)
In 2017, users of the Chanu-Chanu Sports Center in Puno denounced the precarious state of their facilities, questioning satisfaction. For its measurement, the subjective value theory approach was adopted; The study of the quality of service was also incorporated, which measures satisfaction under the paradigm of attitude, consequently the objective of: measuring the relationship between quality of service and user satisfaction of the Chanu-Chanu Puno-Peru sports center was incorporated. The methodology was of a quantitative approach, not experimental, of a correlational type and of a cross-sectional design. With a sample of 308 users from a population of 1608, in a range of 1 month. Results: between quality of service and satisfaction there is a correlation of 0.623. Conclusion: as the quality of service improves, satisfaction will increase and vice versa, however, the change in one variable does not determine the change in the other due to its degree of correlation.